Cocoa - Wentk, Richard (Developer references., 2010)
Develop applications for Mac OS X with this Developer Reference guide Make a clean transition to programming in Apple environments using the elegant and dynamic programming API Cocoa and this practical guide. Written by aseasoned Mac expert, this book shows you how to write programs in Cocoa for the rapidly expanding world of Macintosh users.